Reconstruction of Bandung Groundwater Basin Model Using Schlumberger Configuration Geoelectric Method - Bayu Himawan; Rian Amukti; Friska Agustin; Mochamad Mussoddaq; Andika Artyanto (Universitas Negeri Malang, 2021)
Bandung is a city with rapid industrial development and a dense population. It causes the need for clean water to be huge, so it impacts groundwater extraction on a large scale. The Bandung Basin, which is a good reservoir for groundwater, will be disturbed if conservation and monitoring efforts are not carried out in the presence of groundwater. This study focuses on reconstructing the groundwater model in the Bandung Basin using the Schlumberger geoelectric method. After taking and analyzing the data, it was found that the resistivity value of the location of the presence of groundwater is depicted into three groundwater basins, namely the Bandung-Soreang groundwater basin, the Lembang groundwater basin, and the Batujajar groundwater basin. Unfettered aquifers, relatively aquitard in nature, are in the upper layer of the coal sandstone, claystone and sandstone units. The confined aquifer in the sand unit is under the sandy claystone layer.DOI: 10.17977/um024v6i22021p083